Discovery of semantic web services - Wang, Xiaolan. (2008)
With the increasing growth in popularity of Web services, discovery of relevant Web services becomes a significant challenge. Semantic Web Services are then introduced. Semantic Web services are annotated base on shared ontologies; these annotations are used for semantically discover relevant Web Services. In this thesis, the state-of-the-art tech-nologies of Semantic Web Services, especially semantic approaches used in discovery of Semantic Web Services are examined.